2015
DOI: 10.1111/jnc.13417
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 reduces evoked hippocampal acetylcholine release in adult mice

Abstract: Apolipoprotein E4 (apoE4) is the most prevalent genetic risk factor for Alzheimer's disease. We utilized apoE4-targeted replacement mice (approved by the Tel Aviv University Animal Care Committee) to investigate whether cholinergic dysfunction, which increases during aging and is a hallmark of Alzheimer's disease, is accentuated by apoE4. This revealed that levels of the pre-synaptic cholinergic marker, vesicular acetylcholine transporter in the hippocampus and the corresponding electrically evoked release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…34 The apoE4 protein may also modulate the NMDA receptor directly as NMDA-dependent LTP induction in hippocampal APOE4 slices is lower than slices from APOE3 mice. 35 These changes in intracellular calcium may be responsible for the basal increase in calcineurin activity in the APOE4 mice. Other studies indicate that apoE-containing lipoproteins can protect neurons against oxidative stress by inhibiting the activation of calcineurin.…”
Section: Discussionmentioning
confidence: 99%
“…34 The apoE4 protein may also modulate the NMDA receptor directly as NMDA-dependent LTP induction in hippocampal APOE4 slices is lower than slices from APOE3 mice. 35 These changes in intracellular calcium may be responsible for the basal increase in calcineurin activity in the APOE4 mice. Other studies indicate that apoE-containing lipoproteins can protect neurons against oxidative stress by inhibiting the activation of calcineurin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased acetyl-CoA for acetylcholine synthesis is responsible for decreased transmitter functions in cholinergic neurons of AD patients ( Szutowicz et al, 2013 ). Furthermore, in mice expressing human APOE ε4, evoked hippocampal acetylcholine release is reduced ( Dolejsi et al, 2016 ). Thus, our findings explain the pathological differences between AD APOE ε4 carriers and non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the cognitive change measured by cognitive tests did not show any difference, recent studies found a modulating effect of APOE on treatment response to AChEIs in adult mice [51] and patients with AD [52] using resting state functional connectivity magnetic resonance imaging (rs-fcMRI). Both studies showed better cognitive response in APOE ɛ4 carriers through imaging study.…”
Section: Discussionmentioning
confidence: 99%